CLOSED ABDOMINAL INJURY WITH LIVER DAMAGE - B. V. Sigua; V. P. Zemlyanoy; A. K. Dyukov (Вестник хирургии имени И.И. Грекова)
An analysis of the treatment results was made in 447 patients with closed abdominal injury combined with liver damage. An individualized treatment-and-diagnostic program considering the data of field surgery- MT scale was applied in victims with closed abdominal trauma with liver damage. At the same time the classification E. Moore et.all (1990) for liver injuries was used for assistance. The indications for endovideosurgical homeostasis, a primary suture of liver wound and the hepatic resection were determined. The indications for packing the liver wound were specialized using strategy of «Damage control». An application of given individualized surgical strategy allowed reduction of the lethality level from 32,3% to 17,1% in the case of closed abdominal trauma with liver damage.